Mother's education and birth weight - Arnaud Chevalier; Vincent O'Sullivan (Institute for the Study of Labor (IZA), 2007)
Low birth weight has considerable short and long-term consequences and leads to high costs to the individual and society even in a developed economy. Low birth weight is partially a consequence of choices made by the mother pre- and during pregnancy. Thus policies affecting these choices could have large returns. Using British data, maternal education is found to be positively correlated with birth weight. We identify a causal effect of education using the 1947 reform of the minimum school leaving age. Change in compulsory school leaving age has been previously used as an instrument, but has been criticised for mostly picking up time trends. Here, we demonstrate that the policy effects differ by social background and hence provide identification across cohorts but also within cohort. We find modest but heterogenous positive effects of maternal education on birth weight with an increase from the baseline weight ranging from 2% to 6%
urn:nbn:de:101:1-20080416225
Keywords: 330; Kinder; Gesundheit; Mütter; Bildungsniveau; Großbritannien